2022
DOI: 10.1039/d2ja00065b
|View full text |Cite
|
Sign up to set email alerts
|

On the delayed emission from a laser-produced aluminum plasma under an argon environment

Abstract: In this article, we report rather long time emission ( 250 μs) from aluminum neutrals (Al I) in ns laser produced plasma in the presence of ambient argon. The study...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Arora et al 132 investigated the detection ns-LIBS emission signals from Al I lines at long delay times (≥200 μs) in an Ar atmosphere, under different conditions of laser power density, distance from the target and pressure. The authors considered that the excitation and subsequent emission from neutral Al species might be the result of energy transfer from metastable species of Ar.…”
Section: Laser-based Atomic Spectrometrymentioning
confidence: 99%
“…Arora et al 132 investigated the detection ns-LIBS emission signals from Al I lines at long delay times (≥200 μs) in an Ar atmosphere, under different conditions of laser power density, distance from the target and pressure. The authors considered that the excitation and subsequent emission from neutral Al species might be the result of energy transfer from metastable species of Ar.…”
Section: Laser-based Atomic Spectrometrymentioning
confidence: 99%
“…At a background pressure of 100 mbar, the plasma plume will face a substantial drag as it moves away 22,23 and the plasma plume almost becomes stagnant. Also signicant mixing between the background species and plasma constituents is expected 24 and the instabilities like Rayleigh-Taylor (RT) can be present. 3,25 Studies have shown that RT instability and pressure gradients at the plasma front can contribute to the selfgenerated magnetic eld.…”
Section: Jaas Papermentioning
confidence: 99%